Kesetaraan dan Keadilan Gender Dalam Usaha Tani Padi Di Desa Tobing Julu Kec Huristak Kab Padang Lawas - Risalan Basri Harahap (IAIN Padangsidimpuan, 2020)
Rice is one of the main agricultural commodities in Tobing Julu Village, Huristak District, Padang Lawas Regency. Rice farming business in general is the main source of livelihood of the local village community. Men and women each play an important role in managing the rice farming, starting from seeds, plowing, planting, matching, fertilizing, harvesting, lifting from the paddy fields to the roadside to be brought home, cleaning the rice (airing). There is still a gap between women and men. then women experience subordination experiencing multiple workloads. Thus the purpose of this study is to analyze the extent of the relationship between farmers' socioeconomic factors (gender, age and level of education) with gender relations in the division of labor and household gender equality in Tobing Julu Village and to analyze the division of labor between men and women related to local socio-cultural aspects. The location of this research is Tobing Julu Village, Huristak District, Padang Lawas Regency. The results of the analysis show that gender inequalities in the form of subordination and multiple workloads still occur for women, especially in farming as one of the main commodities to fulfill the family's needs